Effect of forage type on cecal and fecal fermentation parameters in the horse - Lesh, Jessica R.; Sorensen, Rachel J.; Drouillard, James S.; Douthit, Teresa L.; Lattimer, James M. (My University, 2019)
It is well documented that the microbiota of the equine hindgut is easily modified by dietary changes. However, the effect of forage type on the cecal environment is relatively unknown. Therefore, the purpose of this study was to evaluate the effects of forage type on fermentation parameters within the hindgut of horses. Six cecally-cannulated horses (527 ± 56.6 kg BW; 12 ± 2.04 yr) were used in a crossover, split-plot design with treatment consisting of ad libitum access to Smooth Bromegrass hay (brome) or alfalfa hay. Subplots consisted of time and location within horse (cecum vs rectum). Horses were acclimated to their respective treatment for 21 d followed by a 24 h collection period. Horses were then switched to their subsequent diet and the protocol repeated. During the collection period, fecal and cecal samples were collected every 3 h and analyzed for pH and volatile fatty acids (VFA). Data were analyzed using the GLIMMIX procedure in SAS 9.4 with fixed effects of forage, location, and time and random effect of horse and period. Fecal pH of alfalfa-fed horses was greater (P<0.05) when compared to cecal pH in alfalfa-fed horses and fecal pH of brome-fed horses. Acetate, propionate, butyrate, and total VFA concentrations were greater (P<0.05) in the cecum and rectum of alfalfa-fed horses compared to the cecum and rectum of brome-fed horses. Acetate:Propionate was greater in the cecum of alfalfa-fed horses (P<0.05) and compared to the cecum of brome-fed horses (P<0.05). No effect (P>0.10) of location on VFA concentration or pH was found with horses consuming brome. Horses consuming alfalfa had greater (P<0.05) VFA concentrations in the cecum compared to the rectum. Alfalfa provided greater VFA for energy utilization.
Keywords: Spring 2019